Hannah Coulter : a novel - Berry, Wendell, 1934- (Shoemaker & Hoard, an imprint of Avalon Publishing Group, Inc., 2004)
In the latest installment in Wendell Berry's long story about the citizens of Port William, Hannah Coulter remembers. Her first husband, Virgil, was declared "missing in action" shortly after the Battle of the Bulge, and after she married Nathan Coulter about all he could tell Hannah about the Battle of Okinawa was "Ignorant boys, killing each other." The community was stunned and diminished by the war, with some of its sons lost forever and others returning home determined to carry on. Now, in her late seventies, twice-widowed and alone, Hannah sorts through her memories: of her childhood, of young love and loss, of raising children and the changing seasons. She turns her plain gaze to a community facing its long deterioration, where, she says, "We feel the old fabric torn, pulling apart, and we know how much we have loved each other." Hannah offers her summation: her stories and her gratitude, for the membership in Port William, and for her whole life, a part of the great continuum of love and memory, grief and strength.